Migration and integration in Singapore policies and practice (Routledge research on public and social policy in Asia, 2015)
"Between 2000 and 2010, Singapore witnessed a huge influx of foreign migrants. The proportion of permanent residents in the total population increased from 7% to 11%, while the share of non-resident foreigners has risen from 19% to 25%. This was as much the result of the spontaneous movement of labour to economic opportunities, as it was of active policy direction by the Singapore government. The social impact, both beneficial and disruptive, of this movement was felt at all levels of society, and brought other attending public policy issues to the fore. Taking a multi-disciplinary approach, this book examines the social, economic, and political issues that have arisen with the influx of foreigners in Singapore since the turn of the 21st century. Drawing on empirical research, it documents the impact of increasing levels of immigration, and provides an analysis of the longer-term implications of these trends, with each chapter covering a different aspect of socio-cultural, political, or economic outcome arising from intercultural contact and adaptation. The contributors also provide policy suggestions to ensure Singapore continues to be a harmonious nation and a cosmopolitan and vibrant global city"..